2017
DOI: 10.1177/0040517517716902
|View full text |Cite
|
Sign up to set email alerts
|

The selection of a retting method for the extraction of bast fibers as response to challenges in composite reinforcement

Abstract: This article presents an evaluation of bast fiber properties conditioned by the selection of a retting method in terms of meeting requirements for the final application of the fibers as composite reinforcement. Two different methods of fiber extraction were used in the experiment: dew retting and osmotic degumming. The fibrous material was extracted from flax (Modran variety) and hemp (Bialobrzeskie variety). In addition, retted kenaf fibers (from China) were evaluated for the comparison of fiber properties. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The infrared spectra of the tested fibers ( Figure 7 , Figure 8 and Figure 9 ) serve to identify the absorbance ranges that represent vibrations of such functional groups as: O-H, C=O, C=C, COO, C-H, CH 2 , CH 3 , COC [ 20 , 21 ]. The characteristics of the main absorbance spectra in the FTIR of the tested fiber are shown in the Table 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared spectra of the tested fibers ( Figure 7 , Figure 8 and Figure 9 ) serve to identify the absorbance ranges that represent vibrations of such functional groups as: O-H, C=O, C=C, COO, C-H, CH 2 , CH 3 , COC [ 20 , 21 ]. The characteristics of the main absorbance spectra in the FTIR of the tested fiber are shown in the Table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose, hemicellulose and pectin all belong to the polysaccharides similar in terms of molecules bonded with glycosidic bonds within the absorbance range at 896 cm −1 [ 20 , 22 , 23 ]. In the cellulose, the molecules are bonded with (1,4)-β-glycosidic bonds, while in hemicellulose and pectin with (1,4)-β and (1,3)-β-glycosidic.…”
Section: Resultsmentioning
confidence: 99%
“…e finest fibre was obtained after 96 hours of osmotic retting with 40 °C working temperature. is fibre retting method claimed to be more suitable for fibre reinforcement applications [93]. On the contrary, Ruan et al [94] introduced radiofrequency treatment to improve retting efficiency in a variety of water-retting temperatures and durations.…”
Section: Water Rettingmentioning
confidence: 99%
“…The percentage values of the share of the main chemical components in hemp fibres provided by different authors are shown in Table 1. The share of chemical components in the fibre depends on several aspects, e.g., hemp plant variety (Table 2), climatic conditions of growing, method of fibre extraction [30,42] and agricultural methods of plant cultivation including climatic conditions. 66.0-72.5 3 14-22 3 0.6-3.5 3 2.4-5.5 3 0.2-0.5 3 67-78 4 16-18 4 0.8 4 3.5-5.5 4 0.7 4 68 5 15 5 0.8 5 10 5…”
Section: Hemp Fibre Chemical Compositionmentioning
confidence: 99%